Reactive Flow Simulation of Micromixers Based On Grid Deformation Techniques - Mierka, Otto; Munir, Maimoona; Spille, Claas; Timmermann, Jens; Schlüter, Michael; Turek, Stefan (Technische Universität Dortmund, 2017)
Process intensification of engineering applications in the framework of reacting flows in micromixer devices attracts the attention of engineers and scientists from various fields. With the steadily increasing available computational resources the traditional experimentally supported investigations may be extended by computational ones. For this purpose, a simulation framework based on state of the art numerical techniques extended with special grid deformation techniques has been developed. Its validation in terms of comparison with computational and experimental results in reacting, as well as in non-reacting frameworks has been performed on the basis of the T-mixer, and SuperFocus mixer, respectively. The computational efficiency of the developed tool is shown to be applicable for optimization tasks, such as reverse engineering purposes.
Ergebnisberichte des Instituts für Angewandte Mathematik;558
Keywords: grid deformation; reactive liquid flow; one-way coupling; stationary simulation; micromixers; 610